The effects of seismic activities following the 30 October 2020 Samos Island earthquakes in Izmir and its surrounding - PAMUKÇU, Oya Ankaya; ÇIRMIK, Ayça; DOĞRU, Fikret; TUŞAT, Ekrem; UYSAL, Fatih; SÖZBILIR, Hasan; AYDIN, Ufuk; ÖZDAĞ, Özkan Cevdet; ULUĞTEKIN, Metehan; ÖZDEMIR, Fulya; ERHAN, Zülfikar (Contributions to Geophysics and Geodesy, 2024)
With the increasing rate of subduction along the Hellenic Arc in the Eastern Mediterranean, the seismic activities of the Aegean plate and Western Anatolia have markedly increased over the past decade. The increase in seismic activity is quite remarkable, starting from the coasts of Çanakkale in the north of Western Anatolia, including Lesbos Island, Samos Island, Kuşadası Bay and Datca. In this context, in order to determine the current deformation after the Samos Island earthquake that occurred on October 30, 2020, measurements were performed at six continuous GNSS stations in and around Izmir. This study is jointly managed by Dokuz Eylül University, with contributions from Konya Technical University and Atatürk University, focusing on both GNSS and seismological analyses. The preliminary results of this investigation include the evaluation of seismic impacts on the continuous GNSS stations from July 1st to December 31st, 2022.